Construction of anger in one successful case of psychodynamic- interpersonal psychotherapy:: Problem (re)formulation and the negotiation of moral context - Madill, Anna (European Journal for Qualitative Research in Psychotherapy, 2009)
This paper provides a worked exemplar of psychotherapy research using conversation analysis inspired discourse analysis with the aim of exploring the usefulness of discursive analysis for qualitative psychotherapy research within a relational centred ethos. The analysis examines how a client came to describe herself as feeling anger towards her mother having previously rejected this understanding earlier in therapy. Specifically, the analysis explicates the process of successful problem (re)formulation, identifying the rhetorical strategies utilised by the therapist and demonstrating how client change may be approached as a discursive achievement. The central tension between discursive and relational centred qualitative psychotherapy research rests on the different understandings of subjectivity at the core of the two perspectives. The paper concludes, however, that the findings of discursive psychotherapy research may still be utilised in the service of relational centred practice. A detailed analysis of psychotherapy dialogue may be revealing in terms of how therapeutic meaning is co-constructed, how change is enabled through talk, and how cultural resources are mobilised within the practices of therapy. Such knowledge has a function, not least, in enhancing the ability of relational centred psychotherapists to be reflexive practitioners.This paper provides a worked exemplar of psychotherapy research using the approach of conversation analysis inspired discourse analysis (CA/DA), sometimes known as discursive psychology (Edwards & Potter, 1992; Potter, 2003; Potter & Wetherell, 1987). Discursive psychology is a well-established perspective within British qualitative methodology which I have utilised elsewhere to examine the processes of psychotherapy interaction (Madill, 2006; Madill &Barkham, 1997; Madill & Doherty, 1994; Madill, Widdicombe & Barkham, 2001). My aim in the present paper is to explore the potential usefulness of discursive analysis for qualitative psychotherapy research within a relational centred ethos. Relational centred qualitative research, as developed by Linda Finlay and Ken Evans (2009, forthcoming) and articulated within the remit of The European Journal for Qualitative Research in Psychotherapy, is an evolving approach which incorporates the following core values: doing research with, as apposed to on, participants; attending the co-construction of shared understandings; and honouring the subjective experience of participants.I present an analysis of extracts from a case of psychodynamic-interpersonal    psychotherapy based on Hobson’s (1985) conversational model. This model has a particular relational focus in assuming clients’ problems arise from relationship disturbances and that the therapeutic encounter is a vehicle for the manifestation, exploration, and modification of such problems. The model is conversational in that intervention consists of therapists’ use of strategies such as negotiation, metaphor, and development of a ‘common feeling language’. Similarly, discursive analysis is relational centred in that it focuses on the co- construction of meaning as it is represented in conversational exchange. The researcher produces an account of the way in which the participants develop an on-going understanding of each other within their conversational encounter and, in doing so, reflects on and articulates his or her own shared sense-making practices.On the other hand, discursive analysis sits less comfortably with other key aspects of relational centred qualitative research. In discursive analysis, subjectivity is understood as textual (produced in and through language) and situated (produced in relation to on-going and historical contingencies) and this can jar with more usual understandings of the person as a reasonably stable centre of experience and source of agency. So, valuing the subjective experience of the research participant - as their truth and the starting point of exploration - is compatible with discursive analysis only to the extent that ‘subjective experience’ is interpreted as the way in which this is communicated to others and the participant’s ‘truth’ considered a context-sensitive account. Doing research with, as opposed to on, participants may also be difficult as the method utilises a counter-intuitive, and possibly impenetrable, understanding of subjectivity which participants may reject, not least because it appears to undermine the felt immediacy of their lived experience.Although there are tensions with some of the core values of relational centred qualitative research, discursive analysis can be a useful approach to understanding the processes of psychotherapy. It has been argued that it is the micro-level questions - the 'when-then' questions - that clinicians make continuously in-session that inform their choice of intervention (Harper, 1995). By implication, it is the micro-, moment-to-moment processes that must be examined if psychotherapy research is to be informative to practitioners. This ‘change process paradigm’ has utilised qualitative methods to examine episodes of clinically meaningful therapy exchanges, considered potential significant change events, studied as sequences and patterns occurring over time (Soldz & McCullough, 2000). The research from which the exemplar is drawn is situated within this change process paradigm and examines how a client came to describe herself as feeling anger towards her mother having previously rejected this understanding earlier in therapy.Clients characteristically present with emotional difficulties and exploration of, or at least orientation to, the client's emotional experience is an essential feature of many therapeutic rationales. Moreover, emotional processes are often considered central in understanding client change in psychotherapy (Greenberg & Watson, 2006). A specific analytical aim here is to understand the process of problem (re)formulation. This is an important topic as identifying problems is a central requirement for therapeutic intervention and has been shown to be “the result of considerable interactional 'work' on the part of the therapist” (Davis, 1986, p.44).Psychotherapy can be regarded primarily a conversational exchange as, at most basic, it is organised on a turn-by-turn basis. It is likely, therefore, to share features in common with ordinary conversations. In fact, formulations are used in ordinary conversation and function to exhibit understanding through providing an explanation, characterisation, explication, or summary of what has gone before (Garfinkel & Sacks, 1970). Hence, discourse analysis, informed by methods designed specifically for the analysis of conversational exchange, would appear a relevant method through which to examine the processes of therapy.